Kelalaian dalam Pelayanan Kefarmasian Implikasi Etis dan Profesional bagi Apoteker Indonesia - Aryanti, Adinda; Tri Umiana Soleha; Zulpakor Oktoba; Ervina Damayanti (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Negligence in pharmaceutical services is a multifaceted issue that significantly impacts patient safety, the quality of healthcare delivery, and the professional reputation of pharmacists in Indonesia. Such negligence can occur at various stages of pharmaceutical services, including prescribing, dispensing, storage, and administration of medication to patients. The causes of negligence are diverse, encompassing excessive workload, inadequate understanding and application of professional ethical codes, ineffective communication between pharmacists and other healthcare professionals, and suboptimal supervisory and audit systems. This study aims to analyze the ethical and professional implications of negligence in pharmaceutical services and to identify preventive efforts that can improve the quality of pharmaceutical services. This study employs a library research method with a qualitative descriptive approach, thoroughly reviewing scientific literature indexed in Sinta and other reputable academic sources to analyze the ethical and professional implications of negligence in pharmaceutical services. Findings reveal that negligence not only violates core professional ethical principles such as beneficence, non-maleficence, and justice but also exposes pharmacists to serious legal and disciplinary sanctions. Furthermore, negligence leads to long-term negative consequences, including diminished public trust in pharmaceutical services and the broader healthcare system, ultimately hindering national efforts to improve healthcare quality. Therefore, this study recommends continuous professional ethics training, strengthening of both internal and external supervisory mechanisms, and the innovative use of information technology to minimize negligence risks in pharmaceutical practice. The implementation of these measures is expected to enhance pharmaceutical service quality, uphold the integrity and dignity of the pharmacist profession, and provide optimal patient protection in Indonesia.